From Thirst to Satiety: The Anterior Mid-Cingulate Cortex and Right Posterior Insula Indicate Dynamic Changes in Incentive Value - Becker, Christoph A.; Flaisch, Tobias; Renner, Britta; Schupp, Harald T. (Frontiers in Human Neuroscience, 2017)
The cingulate cortex and insula are among the neural structures whose activations have been modulated in functional imaging studies examining discrete states of thirst and drinking to satiation. Building upon these findings, the present study aimed to identify neural structures that change their pattern of activation elicited by water held in the mouth in relation to the internal body state, i.e. proportional to continuous water consumption. Accordingly, participants in a thirsty state were scanned while receiving increments of water until satiety was reached. As expected, fluid ingestion led to a clear decrease in self-reported thirst and the pleasantness ratings of the water ingested. Furthermore, linear decreases in the blood oxygenation level dependent (BOLD) response to water ingestion were observed in the anterior mid-cingulate cortex (aMCC) and right posterior insula as participants shifted towards the non-thirsty state. In addition, regions in the superior temporal gyrus, supplementary motor area, superior parietal lobule, precuneus, and calcarine sulcus also showed a linear decrease with increasing fluid consumption. Further analyses related single trial BOLD responses of associated regions to trial-by-trial ratings of thirst and pleasantness. Overall, the aMCC and posterior insula may be key sites of a neural network representing the motivation for drinking based on the dynamic integration of internal state and external stimuli.